2006 Optical Fiber Communication Conference and the National Fiber Optic Engineers Conference 2006
DOI: 10.1109/ofc.2006.216038
|View full text |Cite
|
Sign up to set email alerts
|

Four-fold reduction in the speed of light at practical power levels using Brillouin scattering in a 2-m Bismuth-oxide fiber

Abstract: A 2-m long Bismuth-oxide-based highly-nonlinear fiber is used to generate Brillouinassisted slow-light. Time delays of 46-ns and a four-fold reduction in the speed of light are achieved for 1 80-ns pulses with a CW pump power ofjust -400-mW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
(9 reference statements)
2
12
0
Order By: Relevance
“…All these aspects highlight the necessity of the efficiency enhancement in the slow light generation for more practicality. In a recent experiment, the use of a 2-m Bismuth-oxide highly nonlinear fiber (Bi-HNLF) was reported to generate 29-dB Brillouin gain and the resultant optical delay of 46 ns with 410-mW pump power [13]. As another experiments, it has been lately reported that a As 2 Se 3 chalcogenide fiber can offer very high Brillouin amplification [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…All these aspects highlight the necessity of the efficiency enhancement in the slow light generation for more practicality. In a recent experiment, the use of a 2-m Bismuth-oxide highly nonlinear fiber (Bi-HNLF) was reported to generate 29-dB Brillouin gain and the resultant optical delay of 46 ns with 410-mW pump power [13]. As another experiments, it has been lately reported that a As 2 Se 3 chalcogenide fiber can offer very high Brillouin amplification [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The FOM of the As 2 Se 3 fiber is calculated to be 0.079 dB/mW/m (0.71 dB/mW, 3.2 m, n=2.81), which is more than 4 times larger than the result of the Bi-HNLF (~ 0.019 dB/mW/m; 29 dB/410 mW, 1.67 m, n=2.22) [13] and 110 times better than observed in a conventional single-mode fiber (~ 0.00072 dB/mW/m; 21 dB/10 W, 2 m, n=1.45) [10]. It must be pointed out that these FOM's were all evaluated from data obtained in short fibers, so that the birefringence can be considered as uniform and the effect of random polarization change along the fiber can be fully neglected.…”
Section: Experiments and Resultsmentioning
confidence: 84%
“…We used this last, fairly simple expression to compare the most representative fibers considered so far: silica [7,22], high-nonlinearity bismuth fiber [11,23], As 2 Se 3 fiber [12], along with the results reported here. The comparison is provided in Table 3, with all the data reported for experiments without polarization control (k = 0.5).…”
Section: Fom Gain½dbmentioning
confidence: 99%
“…Since the standard silica fibers have a very small Brillouin gain coefficient, there is a need for alternative materials with higher values of the gain coefficient which will enable low-power solutions. There have been reports of very efficient slow-light generation in Bi-oxide high-nonlinearity fiber [11] and in As 2 Se 3 chalcogenide fiber [12]. A figure of merit (FOM) has also been proposed in order to easily quantify the degree of usefulness of a given fiber when considered for slow-light applications [12].…”
Section: Introductionmentioning
confidence: 99%